PENGARUH MASSA RAGI DAN WAKTU FERMENTASI TERHADAP BIOETANOL DARI BIJI DURIAN - Farida Hanum; Nurhasmawaty Pohan; Mulia Rambe; Ratih Primadony; Mei Ulyana (Talenta Publisher (Universitas Sumatera Utara), 2013)
Bioethanol is the ethanol made from plants that contains starch, sugar, and the others cellulose plants. This study uses durian seeds that contain carbohydrate and sugar as basic material and the purpose is to make bioethanol from durian seeds with the variation of yeast mass added and fermentation time. The variables used were the changes of yeast mass 3%; 6%; and 9%, fermentation pH was 4,5, and fermentation times were 0; 24; 48; 72; and 96 hours. The results of experiment were the bioethanol concentration was 18.9988% at the yeast mass 6% with 48 hour for the fermentation.